Fostering student mental well‐being through supportive learning communities. (11th May 2016) - Conradson, David
Abstract : At a time when a growing proportion of university students appear to be experiencing mental health problems, one form of collective response is to seek to develop supportive learning communities within academic courses and programs. Such communities have the potential to enhance student social connectedness, which can in turn help students to access peer support and to share strategies for coping with the demands of university. The development of supportive learning communities can be regarded as a preventative approach to student mental well‐being, and complements the more individually focused work of mental health professionals. Here I discuss three relatively common pedagogical practices within the discipline of Geography which, in addition to their educational benefits, can be used to foster supportive learning communities. The practices are group work, residential fieldwork, and assignments that invite students to reflect on the aspects of the contemporary university that promote or undermine student mental well‐being. I discuss some of the ways in which these pedagogical practices can help foster student mental well‐being, as well as noting some institutional obstacles to their use. Renforcer le bien‐être mental des étudiants par l'intermédiaire de communautés d'entraide et d'apprentissage: Dans un contexte d'augmentation de la proportion d'étudiants universitaires qui éprouveraient des problèmes de santé mentale, une mesure collective consiste à soutenir le développement de communautés d'entraide et d'apprentissage intégrées aux cours et programmes d'études. Ces communautés contribuent à rehausser la cohésion sociale entre les étudiants qui disposeront alors d'un accès au soutien par les pairs et à des stratégies communes pour faire face aux exigences universitaires. Le développement de communautés d'entraide et d'apprentissage peut se définir comme une approche de prévention en matière de bien‐être mental des étudiants qui complète les services plus axés sur l'individu qu'offrent les professionnels de la santé mentale. Je m'intéresse particulièrement à trois pratiques pédagogiques bien ancrées dans le cursus de la géographie qui, outre leurs bienfaits éducatifs, peuvent servir à renforcer les communautés d'entraide et d'apprentissage. Il s'agit des travaux en équipe, des travaux sur le terrain où les acteurs résident ensemble, et des travaux scolaires qui amènent les étudiants à se pencher sur les éléments propres au milieu universitaire d'aujourd'hui qui sont bénéfiques ou nuisibles à leur bien‐être mental. Je décris les manières par lesquelles ces pratiques pédagogiques peuvent contribuer à renforcer le bien‐être mental des étudiants, tout en identifiant quelques obstacles institutionnels qui entravent leur mise en œuvre. Key Messages: The proportion of contemporary university students experiencing mental distress appears to be increasing. The development of supportive learning communities is a preventative and collectively oriented response to student mental distress, and complements the individually focused work of mental health professionals. Three relatively common pedagogical practices within Geography—group work, residential fieldwork, and reflective assignments—can be used to develop supportive learning communities.